Demonstration of intrahepatic accumulated microbubble on ultrasound represents the grade of hepatic fibrosis - Ishibashi, Hiroyuki (Springer-Verlag, 2011)
OBJECTIVES: To examine the feasibility of perflubutane-based ultrasound for grading hepatic fibrosis. METHODS: This prospective study included 202 subjects; main study (controls:33, F0–1:35, F2:26, F3:23, cirrhosis:29) and subsequent study (controls:16, F0–1:7, F2:20, F3:7, cirrhosis:6). Diagnostic abilities for assessing fibrosis grade were compared between contrast findings and FIB4 (age × AST/[platelet count × ALT(0.5)]). RESULTS: High-power emission produced an intrahepatic band-like structure, and the three-layer appearance was less frequent and monolayer appearance was more frequent in cirrhosis than controls/chronic hepatitis (P < 0.0001). Intensity difference at 15-min phase showed most significant correlation with fibrosis grade (ρ = 0.79, P < 0.0001), and the best areas under the receiver operating characteristic curves are 0.88 for marked fibrosis, 0.95 for advanced fibrosis and 0.97 for cirrhosis, which were significantly higher than those of FIB4, 0.85 for marked fibrosis, 0.89 for advanced fibrosis and 0.90 for cirrhosis. Sensitivity, specificity and efficiency of the intensity difference were 88%, 72% and 81% for marked fibrosis, 85%, 91% and 89% for advanced fibrosis and 97%, 90% and 91% for cirrhosis, respectively. The subsequent study validated the main study results; significant correlation between the intensity difference and the fibrosis grade (ρ = 0.73–0.77, P < 0.0001). CONCLUSIONS: Perflubutane-based ultrasound accurately predicts the grade of hepatic fibrosis. KEY POINTS: • The behaviour of intrahepatic microbubbles depends on the severity of hepatic fibrosis. • Layer enhancement pattern simply represents the degree of chronic liver disease. • Parenchymal intensity change due to high-power emission predicts the hepatic fibrosis grade.